2019
DOI: 10.1186/s12967-019-2115-9
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 promotes resistance to an EZH2 inhibitor through the pRB-E2F pathway: correlation with the progression of myelodysplastic syndrome into acute myeloid leukemia

Abstract: BackgroundMyelodysplastic syndrome (MDS) can progress to acute myeloid leukemia (AML), and conventional chemotherapy (decitabine) does not effectively inhibit tumor cells. Enhancer of zeste homologue 2 (EZH2) and Heme oxygenase-1 (HO-1) are two key factors in patients resistance and deterioration.MethodsIn total, 58 MDS patients were divided into four groups. We analyzed the difference in HO-1 and EZH2 expression among the groups by real-time PCR. After treatment with Hemin or Znpp IX, flow cytometry was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Moreover, HLM006474 could induce cell cycle arrest in the G2/M phase, apoptosis via caspase-3 and p53, and senescence. Meanwhile, it proved that HLM006474 could reduce the viability of lung cancer cell lines (84) and potentially alter the progression of myelodysplastic syndrome into acute myeloid leukemia (85). Meanwhile, Sheldon (86) indicated that in breast cancer, arsenic trioxid could inhibit the dissociation of E2F1 from the tumor suppressor, retinoblastoma protein (pRB) due to changes in pRB phosphorylation which leads to decreased E2F1 transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HLM006474 could induce cell cycle arrest in the G2/M phase, apoptosis via caspase-3 and p53, and senescence. Meanwhile, it proved that HLM006474 could reduce the viability of lung cancer cell lines (84) and potentially alter the progression of myelodysplastic syndrome into acute myeloid leukemia (85). Meanwhile, Sheldon (86) indicated that in breast cancer, arsenic trioxid could inhibit the dissociation of E2F1 from the tumor suppressor, retinoblastoma protein (pRB) due to changes in pRB phosphorylation which leads to decreased E2F1 transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…NHD13 mice with high expression of EZH2 or EHMT2 rapidly transformed from MDS to AML in a short time, and the survival rate was also notably reduced. He et al (2019) have also clarified that EZH2 is associated with drug resistance and deterioration of MDS, as well as the progression from MDS to AML. Lehnertz et al (2014) have shown that EHMT2 inhibitor can significantly delay the progression of disease and reduce the frequency of leukemia stem cells in a mouse model of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cholangiocarcinoma [ 166 ], acute myeloid leukemia (AML) [ 167 ], and neuroblastoma [ 168 ] show a correlation between high HO-1 expression and poor disease outcomes. Furthermore, HO-1 positivity in chronic myeloid leukemia [ 169 ], acute myeloid leukemia [ 170 ], and myelodysplastic syndrome [ 171 ] correlate with disease progression, resistance to therapy, and relapse.…”
Section: Ho-1 Expression Tumor Aggressiveness and Disease Outcome Evidence From Immunohistochemistrymentioning
confidence: 99%
“…It is worth noting, in melanoma [ 176 ], thyroid cancer [ 172 ], and acute myeloid leukemia [ 167 ], HO-1 positivity correlates with the gain of function mutations of specific oncogenes B-Raf and RET. Moreover, in high-risk and very high-risk myelodysplastic syndrome, HO-1 expression correlates with overexpression of the enhancer of the zeste homologue 2 (EZH2) gene [ 171 ].…”
Section: Ho-1 Expression Tumor Aggressiveness and Disease Outcome Evidence From Immunohistochemistrymentioning
confidence: 99%